Música clássica e estilo no cinema de Hong Sang-soo: parametria e Romantismo europeu - Alvim, Luíza Beatriz (2024)
European classical music is quite present in formal education in East Asia and it is heard in several films by South Korean filmmaker Hong Sang-soo. It is a repertoire of his taste, as reported in interviews, and the director is active in the creation and choice of music in most of his films, a procedure that corresponds to Gorbman’s concept (2007) "auteur music". Hong has been widely studied for his narrative, defined by Medeiros (2018) as parametric, based on Bordwell, but this work focus on the use of music, with film analysis of three feature films that have relationships with European musical and pictorial Romanticism. These are demonstrated during some of the extracts of the films with classical music. In Nobody's daughter (2013), Beethoven’s music is part of the parametric structure. In On the beach at night alone (2017), Schubert’s music marks key structural and melancholic moments. In these two films, the images of the musical moments can be related to paintings by German romantic Caspar David Friedrich. In Grass (2018), Schubert and Wagner are on the background of tense dialogues, and there are relationships between the movements of the dialogues and those of the music.